Personal Data Protection: Cybersecurity Architecture in Georgia - Ekaterina Zakaradze; Khatuna Muradishvili (European Scientific Journal, ESJ, 2025)
The modern world, with its growing dynamics, is becoming increasingly dependent on the digital realm. As a result of technological revolutions, digital technologies have become not only an integral part of daily human life but also one of the key instruments for regulating the relationship between the state and individuals. Against the backdrop of such changes, the need to develop mechanisms for protecting the digital world has emerged, in order to safeguard the essential data that is used for identifying individuals. Thus, the pace of technological development and the forms of personal data processing affect each of us in various ways on a daily basis. Consequently, a new challenge has arisen for the world: to develop a legal framework regarding the inviolability of private life and personal data protection.In Georgia, the protection of human rights and the processing of personal information is a top priority for the government. To achieve this, it is important to develop mechanisms that, on one hand, meet internationally recognized standards, and on the other hand, are precisely aligned with the current stage of Georgia’s digital development. Another significant challenge facing the Georgian state is the analysis and monitoring of cybersecurity issues, as cyberattacks represent a serious threat to personal data protection.